Association between Eating-Fasting and Sleep-Wake Cycles with Eating Times and Food Consumption throughout the Day: Longitudinal Study with Pregnant Women - Pereira, Cecília Silva; Balieiro, Laura Cristina Tibiletti; Teixeira, Gabriela Pereira; Gontijo, Cristiana Araújo; Marot, Luisa Pereira; Fahmy, Walid Makin; Crispim, Cibele Aparecida; Maia, Yara Cristina de Paiva (Sleep Science, 2024)
Objective To investigate the associations of the sleep–eating interval with eating times and food consumption throughout the day in pregnant women.Materials and Methods A longitudinal study with 100 pregnant women treated at the public health network in the city of Uberlândia, state of Minas Gerais (MG), Brazil, during the entire gestational period. The time intervals between waking up and the first eating episode and between the last eating episode and going to sleep (independent variables) were investigated. Outcome measures were meal and sleep times, as well as food consumption throughout the day.Results Food consumption closer to sleep at night is associated with higher total daily caloric intake in the first (β = −0.337, p = 0.016) and second trimesters (Ts) of pregnancy (β = −0.240, p = 0.023), and with longer sleep duration on weekdays (p < 0.05 for all three trimesters). We did not find associations between the wake-up to first eating episode interval and total calories (p > 0.05 for all three trimesters), but the longer this interval, the greater the percentage of calories at dinner (1T: β = 0.266, p = 0.003; 2T: β = 0.269, p = 0.045) and at the last meal (1T: β = 0.324, p = 0.001; 2T: β = 0.231, p = 0.033).Discussion Taking longer to eat the first meal after waking up is associated with higher caloric intake later in the day, while taking longer to sleep after eating the last meal is associated with higher total daily caloric intake and shorter sleep duration, especially in the beginning and middle of pregnancy.
Keywords: food consumption; chrononutrition; gestation; mealtimes; sleep